A solderless diffusion bonded reaction sintered silicon carbide specialty ceramic assembly and method of making same
Patent Information
- Application Number
- CN202610812969.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-06-08
AI Technical Summary
随后依次通过真空浸渍与涂覆,在界面构建梯度层,组件装配后,在轴向压力及受控气氛下进行反应烧结,利用界面微结构产生的毛细管压力差诱导基体内部液相硅定向迁移填充界面,并通过不同碳源的反应时序差异及原位生成碳化硅的体积膨胀效应切断流失通道,有效解决了本体硅流失难题,从而满足实际生产的需要
[0044]与现有技术相比,本发明的有益效果为:本发明通过诱导基体同质组分迁移实现连接,使得制备的特种陶瓷组件在强度方面与母材保持高度一致,尤其适用于陶瓷阀、陶瓷汽缸阀门片等对力学性能和结构完整性要求严苛的特种陶瓷制品;其次,本发明利用界面微纳结构与颗粒级配产生的毛细管压力梯度作为内驱动力,配合非焊接面的物理阻隔层,实现液相的主动输运,有助于阀片类复杂界面结构的均匀致密填充;最后,本发明通过引入具有不同反应活性与形貌特征的多级碳源体系,利用反应时序差异,使界面区液相硅与碳源逐步发生原位反应,在碳骨架位置生成连续的碳化硅固相网络,从而在完成界面填充后切断液相流失通道,有效解决了无焊料反应烧结过程中常见的基体贫硅疏松与接头不致密缺陷,提升陶瓷阀及陶瓷汽缸阀门片在高温、高压、腐蚀介质等苛刻工况下的密封性能与使用寿命。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of special ceramics preparation technology, and relates to a solderless diffusion-welded reaction sintered silicon carbide special ceramic component and its preparation method. Background Technology
[0002] Reactive silicon carbide ceramics, with their excellent high-temperature resistance, wear resistance, and corrosion resistance, have broad application prospects in the manufacturing of special ceramic products, especially in key components such as ceramic valves and ceramic cylinder valve plates. However, due to the high hardness and brittleness of the material itself and limitations in the molding process, it is difficult to directly manufacture large-sized or integral components with complex internal flow channel structures. Therefore, it is usually necessary to assemble simple-shaped ceramic monomers into complex components through joining techniques. Existing silicon carbide ceramic joining technologies mainly include brazing and conventional reactive joining. Brazing usually introduces metal or glass-based filler metals, which not only introduces a heterogeneous interface at the joint, but also the melting point and corrosion resistance of the filler metal are much lower than those of the silicon carbide base material, making the joint a weak link in high-temperature service environments and unable to meet the requirements of ceramic valve plates and other products used under all operating conditions. Although traditional reactive joining technology can achieve relatively high bonding strength, it mostly requires the pre-placement of an external silicon source or silicon-containing paste at the joining interface. This method is difficult to precisely control the amount of silicon infiltration, which can easily lead to silicon enrichment or uneven reaction in the joint area. Moreover, the process is cumbersome and cannot achieve a truly seamless and dense connection.
[0003] To overcome the aforementioned shortcomings, solderless diffusion welding technology, which utilizes the free silicon inherent in the reaction-sintered silicon carbide matrix as a bonding medium, has emerged. However, this technology faces severe challenges in the practical application of this technology in the manufacture of special ceramic products such as ceramic valves and ceramic cylinder valve plates: during the high-temperature sintering process, the liquid-phase silicon inside the matrix is prone to disordered flow or surface volatilization under unconstrained conditions, leading to severe silicon-depleted porosity in the matrix, thereby significantly reducing the mechanical properties of the base material; at the same time, the lack of an effective driving mechanism makes it difficult for the internal silicon to migrate directionally to the interface to be welded, resulting in insufficient interface filling and difficulty in forming a dense metallurgical bond, ultimately affecting the sealing performance and reliability of valve plate components. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component and its preparation method. First, a green blank containing metallic silicon is prepared, and a microgroove structure is processed on the end face to be welded. Subsequently, a gradient layer is constructed at the interface through vacuum impregnation and coating. After assembly, the component undergoes reaction sintering under axial pressure and a controlled atmosphere. The capillary pressure difference generated by the interface microstructure induces the directional migration of liquid-phase silicon within the matrix to fill the interface. Furthermore, the differences in the reaction timing of different carbon sources and the volume expansion effect of in-situ generated silicon carbide cut off the loss channels, effectively solving the problem of bulk silicon loss and thus meeting the needs of practical production.
[0005] To achieve this objective, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component, the method comprising:
[0007] S1, α-SiC powder, colloidal graphite powder, PMMA (polymethyl methacrylate) microspheres and metallic silicon powder are dry mixed, and then PVA (polyvinyl alcohol) aqueous solution is added to granulate to obtain granulated powder. The powder is then cold isostatically pressed to obtain a green blank. The end face of the green blank to be welded is placed in a femtosecond laser processing equipment for laser processing. After the laser processing is completed, hexagonal boron nitride powder and alumina powder are dispersed in an ethanol aqueous solution to obtain a slurry. The slurry is sprayed on the non-welding surface of the green blank and dried to obtain a blank.
[0008] S2, mix anhydrous ethanol, n-butanol and deionized water, add carbon black N330, β-SiC whiskers and polyethyleneimine to obtain suspension A, vertically immerse the end face of the blank to be welded into suspension A, vacuum pressure, and dry to obtain green blank A.
[0009] S3, thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder and silicon powder are added to anhydrous ethanol to obtain suspension B. Suspension B is screen printed on the end face of the green blank A to be welded and dried to obtain the treated green blank.
[0010] S4. Place two processed green blanks on an optical alignment platform and perform an alignment step to obtain an assembly. Place the assembly into a vacuum carbon tube furnace and perform a sintering process to obtain a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component.
[0011] Specifically, it includes:
[0012] S1, α-SiC powder, colloidal graphite powder, PMMA microspheres and metallic silicon powder are dry mixed, and then PVA aqueous solution is added to obtain wet material. Spray granulation is used to obtain granulated powder. The granulated powder is loaded into a mold and cold isostatically pressed to obtain a green blank. The end face of the green blank to be welded is placed in a femtosecond laser processing equipment for laser processing. After the laser processing is completed, hexagonal boron nitride powder and alumina powder are dispersed in an ethanol aqueous solution and ball milled to obtain a slurry. The slurry is sprayed on the non-welding surface of the green blank and dried to obtain a blank.
[0013] S2, mix anhydrous ethanol, n-butanol and deionized water, add carbon black N330, β-SiC whiskers and polyethyleneimine and stir to obtain suspension A, vertically immerse the end face of the blank to be welded into suspension A, vacuum pressure, and dry to obtain green blank A.
[0014] S3, thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder and silicon powder are added to anhydrous ethanol and stirred to obtain suspension B. Suspension B is screen printed on the end face of the green blank A to be welded and dried to obtain the treated green blank.
[0015] S4. Place two processed green blanks on an optical alignment platform and perform an alignment step to obtain an assembly. Place the assembly into a vacuum carbon tube furnace and perform a sintering process to obtain a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component.
[0016] In step S1, when the femtosecond laser scans the end face to be welded, local material is removed and undergoes limited remelting and resolidification in a very short time, forming microgrooves with a cross-sectional profile close to rectangles or trapezoids. The bottom and walls of the grooves have a certain roughness and resolidification texture. This surface morphology provides a geometric channel for the subsequent directional flow of liquid silicon and interfacial reactions. Hexagonal boron nitride and alumina are dispersed in an ethanol-water solution, sprayed onto the non-welding surface, and dried to form a ceramic barrier layer mainly composed of BN and interspersed with Al2O3 particles. This layer is mainly mechanically interlocked with the substrate and does not undergo significant chemical reactions with SiC. It maintains a solid state during subsequent heating and exhibits low wettability to liquid silicon. In the BN / Al2O3 composite coating, hexagonal boron nitride is the main functional component. Its layered crystal structure and low surface energy characteristics make it naturally non-wetting to liquid silicon. Alumina particles are dispersed between the BN layers, mainly playing a role in enhancing the mechanical integrity of the coating and the mechanical interlocking strength with the substrate. Within the reaction sintering temperature range (1540-1610℃), the chemical inertness of BN prevents it from reacting with liquid silicon. Al2O3 particles are encapsulated and isolated by BN sheets, limiting their direct contact area with liquid silicon. Furthermore, within this temperature range, the carbothermic reduction reaction of Al2O3 with Si requires a higher temperature or the participation of carbon to proceed significantly. Therefore, under Ar atmosphere protection during sintering, the coating maintains overall chemical stability and structural integrity. The multiple stacking of BN sheets effectively blocks the penetration path of liquid silicon, which helps to limit the seepage of silicon melt from the sides and bottom.
[0017] In step S2, polyethyleneimine is partially protonated and becomes positively charged in the aqueous phase, adsorbing onto the surfaces of carbon black and β-SiC whiskers, thus giving the particle surfaces a positive charge. When the blank end face to be welded is immersed in suspension A and a vacuum is applied, the external suspension enters the microgrooves and open pores under the combined drive of external pressure difference and capillary action. During the subsequent drying process, the mixed solvent gradually evaporates, leaving polyethyleneimine on the particle surface. The carbon black particles and β-SiC whiskers are fixed in the inner wall of the microgrooves and in the gaps between SiC particles. The carbon black is distributed in a near-continuous or locally agglomerated manner, and the whiskers form bridging structures across the gaps between particles. This reduces the effective pore size in the area near the end face and inside the microgrooves compared to the original pore size inside the matrix, while simultaneously introducing a uniformly distributed carbon source and existing SiC crystal fragments at the micro-interface.
[0018] In step S3, thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder, and fine silica powder are mixed in anhydrous ethanol to form suspension B. This suspension is then screen-printed onto the end face treated with suspension A. The continuous resin phase wets and spreads on the end face and in the microgroove area. The mesophase carbon microspheres and graphite flakes are encapsulated by the resin and deposited on the surface and in shallow pores. Silica powder is dispersed between the resin and carbonaceous particles. After printing, during the drying stage, the ethanol evaporates, and the phenolic resin undergoes condensation and cross-linking reactions, gradually transforming from a linear or low-crosslinking structure to a three-dimensional cross-linked network structure. The coating changes from a flowable state to a solid thermosetting resin-based composite layer, forming a continuous covering layer containing resin residue, carbonaceous particles, and fine silica powder at the interface.
[0019] In step S4, at the initial stage of the sintering process, the phenolic resin gradually transforms from a cross-linked network into a carbonized structure, forming a glassy carbon framework dominated by amorphous carbon and containing a small amount of residual heteroatom functional groups. Mesophase carbon microspheres and flake graphite maintain the main crystalline structure and, together with the glassy carbon, constitute the carbonaceous framework layer at the interface. As the temperature continues to rise, the oxygen-containing functional groups on the surface of the colloidal graphite and carbon black particles in suspension A are further removed, and the carbon phase structure transforms into graphitized or disordered layered graphite. At this point, a granular framework structure supported by coarse SiC particles and filled with fine SiC particles is formed inside the matrix, interspersed with pre-embedded metallic silicon particles, residual carbon sources, and interconnecting channels released by the decomposition of PMMA; near the interface, carbon black and SiC whiskers introduced by suspension A and a carbonaceous framework layer formed by suspension B coexist.
[0020] After the temperature is further increased and the environment is switched to vacuum, the residual silica film inside and on the surface of the billet comes into contact with the carbon source and undergoes a carbothermic reduction reaction, generating volatile silicon-containing gas phases and carbon monoxide. The silica layer covering the surface of SiC particles, the surface of metallic silicon particles, and the interfacial carbonaceous skeleton gradually thins, and in some areas is removed, exposing the surfaces of silicon carbide, metallic silicon, and carbon phases. At this stage, the pre-embedded metallic silicon particles still exist in a solid state, gradually approaching a molten state. The amorphous degree of the interfacial carbonaceous skeleton further increases, and local microporous structure rearrangement occurs, forming a multi-scale porous network that facilitates the subsequent infiltration of liquid silicon.
[0021] When the temperature reaches the range where metallic silicon undergoes a solid-liquid phase transition, the metallic silicon particles inside the preform begin to melt, forming a liquid silicon phase. Under the combined influence of capillary action and external atmospheric pressure, the liquid silicon seeps along the interconnected channels in the matrix. Due to the smaller effective pore size in the end-face region caused by suspension A treatment and microgroove processing, the capillary attraction experienced by the liquid silicon in contact with this region is relatively strong. Therefore, the liquid silicon is preferentially attracted to the interfacial microgrooves and near-surface region. Under conditions of switching to an inert gas and maintaining a certain pressure in the furnace, the evaporation rate of the molten silicon decreases, allowing it to maintain a certain volume distribution within the skeleton and interfacial region for a longer period. Due to the low wettability of the BN / Al2O3 coating on the non-welded surface, the liquid silicon struggles to spread on its surface and penetrate deep into the coating's pores; most of the liquid silicon is confined within the pores of the matrix and the microgroove network near the end face.
[0022] After liquid silicon accumulates in the interfacial region, the molten silicon contacts and reacts with the interfacial carbon source. Carbon black particles introduced by suspension A, due to their small particle size and large specific surface area, preferentially dissolve and react upon contact with liquid silicon. Silicon atoms diffuse within the carbon phase and form silicon carbide nuclei with carbon. Silicon carbide grains are concentrated in the carbon black aggregation region and near the inner wall of the microchannels, forming fine silicon carbide grain bands along the interface. Glassy carbon, mesophase carbon microspheres, and flake graphite in the carbonaceous framework layer react with liquid silicon under higher temperatures and insulation conditions. Silicon atoms enter the interior of the carbon layer and react with carbon through a dissolution-diffusion mechanism to generate silicon carbide crystals. The original carbon framework is gradually replaced by a silicon carbide framework. As the above reactions proceed, the liquid silicon in the interfacial region is gradually consumed, while the silicon carbide grains generated in situ at the original locations of the carbon framework connect with each other, forming a dense and continuous silicon carbide solid-phase network. The silicon carbide solid-phase network occupies the original percolation channel space of liquid silicon in the interface region, forming a physical barrier to the continued outflow of liquid silicon, thereby achieving the sealing of liquid silicon and densification of the joint in the interface region.
[0023] As a preferred embodiment of the present invention, in S1, the mass ratio of α-SiC powder, colloidal graphite powder, PMMA microspheres, metallic silicon powder, and PVA aqueous solution is (85-91):(5-6):(5-6):(15-17):(5-10), for example, it can be (85, 85.6, 86.2, 86.8, 87.4, 88, 88.6, 89.2, 89.8, 90.4, or 91):(5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5. 7, 5.8, 5.9 or 6.0: (5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0): (15, 15.2, 15.4, 15.6, 15.8, 16.0, 16.2, 16.4, 16.6, 16.8 or 17): (5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10), but not limited to the listed values; other unlisted values within this range also apply.
[0024] In some optional embodiments, the α-SiC powder is composed of α-SiC powder with a D50 of 45 μm and α-SiC powder with a D50 of 5 μm, in a mass ratio of (60-65):(25-26), for example, (60, 60.5, 61, 61.5, 62, 62.5, 63, 63.5, 64, 64.5 or 65):(25, 25.1, 25.2, 25.3, 25.4, 25.5, 25.6, 25.7, 25.8, 25.9 or 26), but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0025] In some optional embodiments, the D50 of the silicon metal powder is 100 μm.
[0026] In some optional embodiments, the mass fraction of the PVA aqueous solution is 5-10 wt.%, for example, it can be 5 wt.%, 5.5 wt.%, 6 wt.%, 6.5 wt.%, 7 wt.%, 7.5 wt.%, 8 wt.%, 8.5 wt.%, 9 wt.%, 9.5 wt.% or 10 wt.%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0027] In some optional embodiments, the cold isostatic pressing pressure is 250-270 MPa and the time is 3-5 min. For example, the pressure can be (250, 252, 254, 256, 258, 260, 262, 264, 266, 268 or 270) MPa and the time can be (3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 or 5.0) min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0028] In some optional embodiments, the laser processing employs a wavelength of 1020-1040 nm, a pulse width of 250-300 fs, and a surface energy of 0.2-0.5 J / cm². 2 Laser scanning is performed with a scanning speed of 100-300 mm / s to obtain concentric ring or orthogonal mesh microgroove structures with a groove width of 18-22 μm, a groove depth of 28-32 μm, and a groove spacing of 90-110 μm. For example, this could involve using wavelengths of (1020, 1022, 1024, 1026, 1028, 1030, 1032, 1034, 1036, 1038, or 1040) nm, pulse widths of (250, 255, 260, 265, 270, 275, 280, 285, 290, 295, or 300) fs, and surface energy of (0.2, 0.23, 0.26, 0.29, 0.32, 0.35, 0.38, 0.41, 0.44, 0.47, or 0.5) J / cm². 2 Laser scanning was performed with scanning speeds of (100, 120, 140, 160, 180, 200, 220, 240, 260, 280, or 300) mm / s to obtain groove widths of (18, 18.4, 18.8, 19.2, 19.6, 20.0, 20.4, 20.8, 21.2, 21.6, or 22) μm and groove depths of (28, 28.4, ...). The concentric ring or orthogonal grid microgroove structures with groove spacing of (90, 92, 94, 96, 98, 100, 102, 104, 106, 108 or 110) μm are used, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] In some optional embodiments, the mass ratio of the hexagonal boron nitride powder, alumina powder, and ethanol aqueous solution is (3-5):(6-8):(30-40), and the mass fraction of the ethanol aqueous solution is 50 wt.%. For example, the mass ratio can be (3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 or 5.0):(6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8 or 8.0):(30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40), and the mass fraction of the ethanol aqueous solution is 50 wt.%. However, this is not limited to the listed values; other unlisted values within this range are also applicable.
[0030] In some alternative embodiments, the spraying produces a dry film thickness of 50-60 μm, for example, 50 μm, 51 μm, 52 μm, 53 μm, 54 μm, 55 μm, 56 μm, 57 μm, 58 μm, 59 μm or 60 μm, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0031] As a preferred embodiment of the present invention, in S2, the mass ratio of anhydrous ethanol, n-butanol, deionized water, carbon black N330, β-SiC whiskers, and polyethyleneimine is (30-36):(10-12):(5-10):(3-4):(1-2):(0.3-0.5), for example, it can be (30, 30.6, 31.2, 31.8, 32.4, 33.0, 33.6, 34.2, 34.8, 35.4 or 36):(10.0, 10.2, 10.4, 10.6, 10.8, 11.0, 11.2, 11.4, 11.6, 11.8 or 12). .0): (5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10): (3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9 or 4.0): (1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0): (0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48 or 0.5), but not limited to the listed values; other unlisted values within this range also apply.
[0032] In some optional embodiments, the β-SiC whiskers have a diameter of 0.1-0.2 μm and an aspect ratio of 20:1. For example, they can have a diameter of (0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.2) μm and an aspect ratio of 20:1, but are not limited to the listed values. Other unlisted values within this range are also applicable.
[0033] In some alternative embodiments, the pH of suspension A is adjusted to 9-10, for example, to (9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0), but is not limited to the listed values; other unlisted values within this range are also applicable.
[0034] In some optional embodiments, the absolute pressure of the vacuum holding is 500-800 Pa and the time is 240-360 s. For example, the absolute pressure can be (500, 530, 560, 590, 620, 650, 680, 710, 740, 770 or 800) Pa and the time can be (240, 252, 264, 276, 288, 300, 312, 324, 336, 348 or 360) s, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0035] As a preferred embodiment of the present invention, in S3, the mass ratio of the thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder, silicon powder, and anhydrous ethanol is (15-20):(5-7):(3-5):(1-2):(20-30), for example, it can be (15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5 or 20.0):(5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6. 2, 6.4, 6.6, 6.8 or 7.0: (3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 or 5.0): (1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0): (20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30), but not limited to the listed values; other unlisted values within this range also apply.
[0036] In some optional embodiments, the particle size of the mesophase carbon microspheres is 5-10 μm, for example, it can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0037] In some optional embodiments, the particle size of the flake graphite powder is 3-5 μm, for example, it can be 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm or 5.0 μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0038] In some optional embodiments, the D50 of the silicon powder is 0.3-0.5 μm, for example, it can be 0.3 μm, 0.32 μm, 0.34 μm, 0.36 μm, 0.38 μm, 0.4 μm, 0.42 μm, 0.44 μm, 0.46 μm, 0.48 μm or 0.5 μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0039] In some optional embodiments, the viscosity of the suspension B at 25±2°C is 2000-3000 mPa·s, for example, it can be (2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, or 3000) mPa·s at (23, 23.4, 23.8, 24.2, 24.6, 25.0, 25.4, 25.8, 26.2, 26.6, or 27)°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0040] In some optional embodiments, the screen printing mesh count is 250-325 mesh, and the wet film thickness is 23-27 μm. For example, the mesh count can be (250, 257.5, 265, 272.5, 280, 287.5, 295, 302.5, 310, 317.5 or 325) mesh, and the wet film thickness can be (23, 23.4, 23.8, 24.2, 24.6, 25, 25.4, 25.8, 26.2, 26.6 or 27) μm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0041] As a preferred technical solution of the present invention, in S4, the alignment step is as follows: adjust the position so that the coaxiality deviation of the two end faces to be welded is controlled to be no more than 10μm. After alignment, transfer the component to the graphite tooling fixture for clamping and fixing. Apply an axial load of 8-10MPa along the normal direction of the welding end face by means of a screw or hydraulic device, and maintain the loading state for 5-10 minutes to complete the pre-tightening and positioning. For example, it could be: adjust the position to control the coaxiality deviation of the two end faces to be welded to no more than 10μm, align them, transfer the components to a graphite tooling fixture for clamping and fixing, apply an axial load of (8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0) MPa along the normal direction of the welding end face using a screw or hydraulic device, and maintain the loading state for (5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10) min to complete pre-tightening and positioning, but it is not limited to the listed values, other unlisted values within this range are also applicable.
[0042] In some optional embodiments, the sintering procedure is as follows: Ar is introduced at a flow rate of 300-600 sccm, the absolute pressure in the furnace is adjusted to 400-600 Pa, the temperature is increased from room temperature to 600-620°C at a rate of 1°C / min and held for 60-70 min, then increased to 900-920°C at a rate of 2°C / min, then the gas intake is stopped and the vacuum system is turned on to evacuate the furnace to a dynamic vacuum state, then increased to 1415-1425°C at a rate of 5°C / min, and within this temperature range, Ar is introduced, and the furnace pressure is adjusted to 0. At a pressure of 0.09-0.11 MPa, under an Ar atmosphere, the temperature is increased to 1450-1460℃ at a rate of 2℃ / min, then increased to 1540-1560℃ at the same rate and held for 25-35 min. Subsequently, the temperature is increased to 1590-1610℃ and held for 25-35 min to complete the reaction sintering. After sintering, the furnace temperature is reduced to 1340-1360℃ at a cooling rate of 5℃ / min and held for 55-65 min in this temperature range. The heating power is then turned off while maintaining the Ar protective atmosphere, and the furnace is cooled to room temperature.For example, it could be: introducing Ar at a flow rate of (300, 330, 360, 390, 420, 450, 480, 510, 540, 570 or 600) sccm, adjusting the furnace absolute pressure to (400, 420, 440, 460, 480, 500, 520, 540, 560, 580 or 600) Pa, raising the temperature from room temperature to (600, 602, 604, 606, 608, 610, 612, 614, 616, 618 or 620) ℃ at 1 ℃ / min and holding it at (60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70) min, and then raising it to (90) ℃ at 2 ℃ / min. The furnace is evacuated to a dynamic vacuum state by introducing Ar gas at a rate of 0, 902, 904, 906, 908, 910, 912, 914, 916, 918, or 920 °C. The gas intake is then stopped and the vacuum system is activated. The furnace is then raised to a dynamic vacuum state at a rate of 5 °C / min to (1415, 1416, 1417, 1418, 1419, 1420, 1421, 1422, 1423, 1424, or 1425) °C. Within this temperature range, Ar gas is introduced, and the furnace pressure is adjusted to (0.09, 0.092, 0.094, 0.096, 0.098, 0.1, 0.102, 0.104, 0.106, 0.108, or 0.11) MPa. The furnace is then evacuated to an Ar atmosphere at a rate of... Continue heating at 2℃ / min to (1450, 1451, 1452, 1453, 1454, 1455, 1456, 1457, 1458, 1459, or 1460)℃, then continue heating at the same rate to (1540, 1542, 1544, 1546, 1548, 1550, 1552, 1554, 1556, 1558, or 1560)℃ and hold for (25, 26, 27, 28, 29, 30, 31, 32, 33, 34, or 35) min, then continue heating to (1590, 1592, 1594, 1596, 1598, 1600, 1602, 1604, 1606, 1608, or 1460)℃. The reaction sintering is completed by holding the furnace at 610℃ for 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35 minutes. After sintering, the furnace temperature is reduced to 1340, 1342, 1344, 1346, 1348, 1350, 1352, 1354, 1356, 1358 or 1360℃ at a cooling rate of 5℃ / min. The furnace temperature is then held for 55, 56, 57, 58, 59, 60, 61, 62, 63, 64 or 65 minutes. The heating power is then turned off while maintaining an Ar protective atmosphere. The furnace is then cooled to room temperature, but this is not limited to the listed values. Other unlisted values within this range are also applicable.
[0043] In a second aspect, the present invention provides a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component prepared by the preparation method described in the first aspect.
[0044] Compared with existing technologies, the beneficial effects of this invention are as follows: First, this invention achieves connection by inducing the migration of homogeneous components in the matrix, ensuring that the prepared special ceramic components maintain a high degree of consistency with the base material in terms of strength. This is particularly suitable for special ceramic products such as ceramic valves and ceramic cylinder valve plates, which have stringent requirements for mechanical properties and structural integrity. Second, this invention utilizes the capillary pressure gradient generated by the interfacial micro-nano structure and particle gradation as an internal driving force, combined with the physical barrier layer of the non-welded surface, to achieve active transport of the liquid phase, which helps to uniformly and densely fill the complex interfacial structure of valve plates. Finally, this invention introduces a multi-level carbon source system with different reactivity and morphological characteristics, and utilizes the difference in reaction sequence to allow the liquid phase silicon and carbon source in the interfacial region to gradually react in situ, generating a continuous silicon carbide solid network at the carbon skeleton position. This effectively cuts off the liquid phase loss channel after the interface filling is completed, effectively solving the common defects of matrix silicon depletion and loose joints in solderless reaction sintering, and improving the sealing performance and service life of ceramic valves and ceramic cylinder valve plates under harsh conditions such as high temperature, high pressure, and corrosive media. Detailed Implementation
[0045] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments described herein are specific implementations of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the implementation of the present invention or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.
[0046] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone any further purification treatment.
[0047] Example 1
[0048] This embodiment provides a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component and its preparation method. The preparation method specifically includes the following steps:
[0049] S1, 85g of α-SiC powder, 6g of colloidal graphite powder, 5g of PMMA microspheres, and 17g of metallic silicon powder with a D50 of 100μm are dry-mixed. The α-SiC powder consists of α-SiC powder with a D50 of 45μm and α-SiC powder with a D50 of 5μm, in a mass ratio of 60:25. Then, 10g of a 5wt.% PVA aqueous solution is added to obtain a wet material. The wet material is then spray-granulated to obtain granulated powder. The granulated powder is loaded into a mold and cold isostatically pressed to obtain a green compact. The cold isostatic pressing pressure is 250MPa for 5min. The end face of the green compact to be welded is placed in a femtosecond laser processing device for laser processing. The laser processing uses a wavelength of 1040nm, a pulse width of 250fs, and a surface energy of 0.5J / cm². 2 Laser scanning was performed with a scanning speed of 100 mm / s to obtain a concentric annular microgroove structure with a groove width of 22 μm, a groove depth of 28 μm, and a groove spacing of 110 μm. After laser processing, 3 g of hexagonal boron nitride powder and 8 g of alumina powder were dispersed in 30 g of 50 wt.% ethanol aqueous solution and ball-milled to obtain a slurry. The slurry was sprayed onto the non-welded surface of the green blank, and the spraying resulted in a dry film thickness of 60 μm. The green blank was then dried to obtain a raw blank.
[0050] S2, 36g anhydrous ethanol, 10g n-butanol and 10g deionized water are mixed, 4g carbon black N330, 1g β-SiC whiskers and 0.5g polyethyleneimine are added and mixed, wherein the diameter of the β-SiC whiskers is 0.1μm and the aspect ratio is 20:1. The mixture is stirred to obtain suspension A. The pH of suspension A is adjusted to 9. The end face of the blank to be welded is vertically immersed in suspension A and vacuum pressure is maintained. The absolute pressure of the vacuum pressure is 800Pa and the time is 240s. The blank is dried to obtain green blank A.
[0051] S3, 20g of thermosetting phenolic resin, 5g of mesophase carbon microspheres, 5g of flake graphite powder and 1g of silicon powder are added to 30g of anhydrous ethanol and stirred to obtain suspension B. The particle size of the mesophase carbon microspheres is 10μm, the particle size of the flake graphite powder is 3μm, the D50 of the silicon powder is 0.5μm, and the viscosity of suspension B at 23℃ is 2000mPa·s. Suspension B is screen printed onto the end face to be welded of green blank A. The mesh number of the screen printing is 325 mesh, the thickness of the wet film is 23μm, and the processed green blank is obtained after drying.
[0052] S4. Place the two processed green blanks on the optical alignment platform for alignment. The alignment step involves adjusting the position to control the coaxiality deviation of the two end faces to be welded to no more than 10 μm. After alignment, transfer the assembly to a graphite tooling fixture for clamping and fixing. Apply an axial load of 10 MPa along the normal direction of the welding end face using a screw device, maintain the loaded state for 5 minutes to complete pre-tightening and positioning, and obtain the assembly. Place the assembly into a vacuum carbon tube furnace for sintering. The sintering process involves introducing Ar at a flow rate of 300 sccm, adjusting the absolute pressure of the furnace to 600 Pa, raising the temperature from room temperature to 620°C at a rate of 1°C / min and holding for 60 minutes, then increasing the temperature at a rate of 2°C / min. The furnace temperature was raised to 920°C, then the gas intake was stopped and the vacuum system was turned on to evacuate the furnace to a dynamic vacuum state. The temperature was then raised to 1415°C at a rate of 5°C / min. During this temperature range, Ar was introduced, and the furnace pressure was adjusted to 0.11 MPa. Under the Ar atmosphere, the temperature was raised to 1460°C at a rate of 2°C / min, and then raised to 1610°C at the same rate and held for 25 minutes to complete the reaction sintering. After sintering, the furnace temperature was lowered to 1340°C at a cooling rate of 5°C / min and held for 65 minutes. The heating power was turned off and the Ar protective atmosphere was maintained. The furnace was cooled to room temperature to obtain a reaction sintered silicon carbide special ceramic component without solder diffusion welding.
[0053] Example 2
[0054] This embodiment provides a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component and its preparation method. The preparation method specifically includes the following steps:
[0055] S1, 91g of α-SiC powder, 5g of colloidal graphite powder, 6g of PMMA microspheres, and 15g of metallic silicon powder with a D50 of 100μm are dry-mixed. The α-SiC powder consists of α-SiC powder with a D50 of 45μm and α-SiC powder with a D50 of 5μm, in a mass ratio of 65:26. Then, 5g of a 10wt.% PVA aqueous solution is added to obtain a wet material. Spray granulation is used to obtain granulated powder. The granulated powder is loaded into a mold and cold isostatically pressed to obtain a green compact. The cold isostatic pressing pressure is 270MPa for 3min. The end face of the green compact to be welded is placed in a femtosecond laser processing device for laser processing. The laser processing uses a wavelength of 1020nm, a pulse width of 300fs, and a surface energy of 0.2J / cm². 2Laser scanning was performed with a scanning speed of 300 mm / s to obtain a concentric annular microgroove structure with a groove width of 18 μm, a groove depth of 32 μm, and a groove spacing of 90 μm. After laser processing, 5 g of hexagonal boron nitride powder and 6 g of alumina powder were dispersed in 40 g of 50 wt.% ethanol aqueous solution and ball-milled to obtain a slurry. The slurry was sprayed onto the non-welded surface of the green blank, and the spraying resulted in a dry film thickness of 50 μm. The green blank was then dried to obtain a raw blank.
[0056] S2, mix 30g anhydrous ethanol, 12g n-butanol and 5g deionized water, add 3g carbon black N330, 2g β-SiC whiskers and 0.3g polyethyleneimine, wherein the diameter of the β-SiC whiskers is 0.2μm and the aspect ratio is 20:1, stir to obtain suspension A, adjust the pH of suspension A to 10, vertically immerse the end face of the blank to be welded into suspension A, vacuum pressure hold, the absolute pressure of the vacuum pressure hold is 500Pa and the time is 360s, and dry to obtain green blank A;
[0057] S3, 15g of thermosetting phenolic resin, 7g of mesophase carbon microspheres, 3g of flake graphite powder and 2g of silicon powder are added to 20g of anhydrous ethanol and stirred to obtain suspension B. The particle size of the mesophase carbon microspheres is 5μm, the particle size of the flake graphite powder is 5μm, the D50 of the silicon powder is 0.3μm, and the viscosity of suspension B at 27℃ is 3000mPa·s. Suspension B is screen printed onto the end face to be welded of green blank A. The mesh number of the screen printing is 250 mesh, the thickness of the wet film is 27μm, and the processed green blank is obtained after drying.
[0058] S4. Place the two processed green blanks on an optical alignment platform for alignment. The alignment process involves adjusting the position to ensure the coaxiality deviation of the two end faces to be welded is no more than 10 μm. After alignment, transfer the assembly to a graphite fixture for clamping and fixing. Apply an axial load of 8 MPa along the normal direction of the welding end face using a hydraulic device, maintain the load for 10 minutes to complete pre-tightening and positioning, and obtain the assembly. Place the assembly into a vacuum carbon tube furnace for sintering. The sintering process involves introducing Ar at a flow rate of 600 sccm, adjusting the furnace absolute pressure to 400 Pa, raising the temperature from room temperature to 600℃ at a rate of 1℃ / min and holding for 70 minutes, then raising the temperature to 900℃ at a rate of 2℃ / min. The gas intake was then stopped and the vacuum system was turned on to evacuate the furnace to a dynamic vacuum state. The temperature was then increased to 1425°C at a rate of 5°C / min. Within this temperature range, Ar was introduced, and the furnace pressure was adjusted to 0.09 MPa. Under the Ar atmosphere, the temperature was further increased to 1450°C at a rate of 2°C / min, and then increased to 1540°C at the same rate and held for 35 minutes. Subsequently, the temperature was increased to 1590°C and held for 35 minutes to complete the reaction sintering. After sintering, the furnace temperature was reduced to 1360°C at a cooling rate of 5°C / min and held for 55 minutes within this temperature range. The heating power was then turned off, and the Ar protective atmosphere was maintained. The furnace was cooled to room temperature to obtain a reaction sintered silicon carbide special ceramic component without solder diffusion welding.
[0059] Example 3
[0060] This embodiment provides a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component and its preparation method. The preparation method specifically includes the following steps:
[0061] S1, 88g of α-SiC powder, 5.5g of colloidal graphite powder, 5.5g of PMMA microspheres, and 16g of metallic silicon powder with a D50 of 100μm are dry-mixed. The α-SiC powder consists of α-SiC powder with a D50 of 45μm and α-SiC powder with a D50 of 5μm, in a mass ratio of 63:25. Then, 8g of 8wt.% PVA aqueous solution is added to obtain a wet material. Spray granulation is used to obtain granulated powder. The granulated powder is loaded into a mold and cold isostatically pressed to obtain a green compact. The cold isostatic pressing pressure is 260MPa for 4min. The end face of the green compact to be welded is placed in a femtosecond laser processing device for laser processing. The laser processing uses a wavelength of 1030nm, a pulse width of 280fs, and a surface energy of 0.3J / cm². 2Laser scanning was performed with a scanning speed of 200 mm / s to obtain an orthogonal mesh-like microgroove structure with a groove width of 20 μm, a groove depth of 30 μm, and a groove spacing of 100 μm. After laser processing, 4 g of hexagonal boron nitride powder and 7 g of alumina powder were dispersed in 35 g of 50 wt.% ethanol aqueous solution and ball-milled to obtain a slurry. The slurry was sprayed onto the non-welded surface of the green blank, and the spraying resulted in a dry film thickness of 55 μm. The green blank was then dried.
[0062] S2, 32g anhydrous ethanol, 11g n-butanol and 8g deionized water are mixed, and 3.5g carbon black N330, 1.5g β-SiC whiskers and 0.4g polyethyleneimine are added and mixed. The diameter of the β-SiC whiskers is 0.17μm and the aspect ratio is 20:1. The mixture is stirred to obtain suspension A. The pH of suspension A is adjusted to 9.5. The end face of the blank to be welded is vertically immersed in suspension A and vacuum pressure is maintained. The absolute pressure of the vacuum pressure is 600Pa and the time is 300s. The blank is then dried to obtain green blank A.
[0063] S3, 18g of thermosetting phenolic resin, 6g of mesophase carbon microspheres, 4g of flake graphite powder and 1.5g of silicon powder are added to 25g of anhydrous ethanol and stirred to obtain suspension B. The particle size of the mesophase carbon microspheres is 8μm, the particle size of the flake graphite powder is 4μm, the D50 of the silicon powder is 0.4μm, and the viscosity of suspension B at 25℃ is 2500mPa·s. Suspension B is screen printed on the end face to be welded of green blank A. The mesh number of the screen printing is 300 mesh, the thickness of the wet film is 25μm, and the processed green blank is obtained after drying.
[0064] S4. Place the two processed green blanks on an optical alignment platform for alignment. The alignment process involves adjusting the position to ensure the coaxiality deviation of the two end faces to be welded is no more than 10 μm. After alignment, transfer the assembly to a graphite fixture for clamping and fixing. Apply an axial load of 9 MPa along the normal direction of the welding end face using a screw device, maintain the loaded state for 8 minutes to complete pre-tightening and positioning, and obtain the assembly. Place the assembly into a vacuum carbon tube furnace for sintering. The sintering process involves introducing Ar at a flow rate of 450 sccm, adjusting the furnace absolute pressure to 500 Pa, raising the temperature from room temperature to 610°C at a rate of 1°C / min and holding for 65 minutes, then raising the temperature to 910°C at a rate of 2°C / min. The gas intake was then stopped and the vacuum system was turned on to evacuate the furnace to a dynamic vacuum state. The temperature was then increased to 1420°C at a rate of 5°C / min. Within this temperature range, Ar was introduced, and the furnace pressure was adjusted to 0.10 MPa. Under the Ar atmosphere, the temperature was increased to 1455°C at a rate of 2°C / min, and then increased to 1550°C at the same rate and held for 30 minutes. Subsequently, the temperature was increased to 1600°C and held for 30 minutes to complete the reaction sintering. After sintering, the furnace temperature was reduced to 1350°C at a cooling rate of 5°C / min and held for 60 minutes within this temperature range. The heating power was turned off, and the Ar protective atmosphere was maintained. The furnace was then cooled to room temperature to obtain a reaction sintered silicon carbide special ceramic component without solder diffusion welding.
[0065] Example 4
[0066] This embodiment provides a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component and its preparation method. The preparation method specifically includes the following steps:
[0067] S1, 86g of α-SiC powder, 5.2g of colloidal graphite powder, 5.8g of PMMA microspheres, and 16.5g of metallic silicon powder with a D50 of 100μm are dry-mixed. The α-SiC powder consists of α-SiC powder with a D50 of 45μm and α-SiC powder with a D50 of 5μm, in a mass ratio of 60:26. Then, 6g of a 6wt.% PVA aqueous solution is added to obtain a wet material. Spray granulation is used to obtain granulated powder. The granulated powder is loaded into a mold and cold isostatically pressed to obtain a green compact. The cold isostatic pressing pressure is 255MPa for 4.5min. The end face of the green compact to be welded is placed in a femtosecond laser processing device for laser processing. The laser processing uses a wavelength of 1035nm, a pulse width of 260fs, and a surface energy of 0.4J / cm². 2Laser scanning was performed with a scanning speed of 250 mm / s to obtain an orthogonal mesh-like microgroove structure with a groove width of 21 μm, a groove depth of 29 μm, and a groove spacing of 95 μm. After laser processing, 4.5 g of hexagonal boron nitride powder and 6.5 g of alumina powder were dispersed in 38 g of 50 wt.% ethanol aqueous solution and ball-milled to obtain a slurry. The slurry was sprayed onto the non-welded surface of the green blank, and the spraying resulted in a dry film thickness of 58 μm. The green blank was then dried.
[0068] S2, 34g anhydrous ethanol, 11.5g n-butanol and 6g deionized water are mixed, and 3.8g carbon black N330, 1.8g β-SiC whiskers and 0.45g polyethyleneimine are added. The β-SiC whiskers have a diameter of 0.13μm and an aspect ratio of 20:1. The mixture is stirred to obtain suspension A. The pH of suspension A is adjusted to 9.2. The end face of the blank to be welded is vertically immersed in suspension A and vacuum pressure is maintained at an absolute pressure of 700Pa for 280s. The blank is then dried to obtain green blank A.
[0069] S3, 16g of thermosetting phenolic resin, 6.5g of mesophase carbon microspheres, 4.5g of flake graphite powder and 1.2g of silicon powder are added to 28g of anhydrous ethanol and stirred to obtain suspension B. The particle size of the mesophase carbon microspheres is 6μm, the particle size of the flake graphite powder is 4.5μm, the D50 of the silicon powder is 0.45μm, and the viscosity of suspension B at 24℃ is 2800mPa·s. Suspension B is screen printed onto the end face to be welded of green blank A. The mesh number of the screen printing is 280 mesh, the thickness of the wet film is 26μm, and the processed green blank is obtained after drying.
[0070] S4. Place the two processed green blanks on an optical alignment platform for alignment. The alignment process involves adjusting the position to ensure the coaxiality deviation of the two end faces to be welded is no more than 10 μm. After alignment, transfer the assembly to a graphite fixture for clamping and fixing. Apply an axial load of 8.5 MPa along the normal direction of the welding end face using a hydraulic device, maintain the load for 6 minutes to complete pre-tightening and positioning, and obtain the assembly. Place the assembly into a vacuum carbon tube furnace for sintering. The sintering process involves introducing Ar at a flow rate of 500 sccm, adjusting the furnace absolute pressure to 450 Pa, raising the temperature from room temperature to 605°C at a rate of 1°C / min and holding for 68 minutes, then raising the temperature to 905°C at a rate of 2°C / min. The gas intake was then stopped and the vacuum system was turned on to evacuate the furnace to a dynamic vacuum state. The temperature was then increased to 1418°C at a rate of 5°C / min. Within this temperature range, Ar was introduced, and the furnace pressure was adjusted to 0.095 MPa. Under the Ar atmosphere, the temperature was further increased to 1452°C at a rate of 2°C / min, and then increased to 1555°C at the same rate and held for 28 minutes. Subsequently, the temperature was increased to 1605°C and held for 28 minutes to complete the reaction sintering. After sintering, the furnace temperature was reduced to 1345°C at a cooling rate of 5°C / min and held for 58 minutes within this temperature range. The heating power was then turned off while maintaining the Ar protective atmosphere, and the furnace was cooled to room temperature to obtain a reaction sintered silicon carbide special ceramic component without solder diffusion welding.
[0071] Comparative Example 1
[0072] This comparative example provides a solderless diffusion-welded reaction sintered silicon carbide special ceramic component and its preparation method. The difference between this and Example 1 is that femtosecond laser processing is not performed in S1. Instead, the green blank obtained by cold isostatic pressing is simply ground / polished to make the end face to be welded flat. Other process parameters and operating conditions are exactly the same as in Example 1.
[0073] Comparative Example 2
[0074] This comparative example provides a solderless diffusion-welded reaction sintered silicon carbide special ceramic component and its preparation method. The difference between this example and Example 1 is that the blank is not subjected to vacuum impregnation treatment with suspension A in S2. Other process parameters and operating conditions are exactly the same as in Example 1.
[0075] Comparative Example 3
[0076] This comparative example provides a solderless diffusion-welded reaction sintered silicon carbide special ceramic component and its preparation method. The difference between this and Example 1 is that step S3 is not performed, i.e., suspension B is not prepared, and screen printing coating is not performed on the end face to be welded after treatment with suspension A. Other process parameters and operating conditions are exactly the same as in Example 1.
[0077] Comparative Example 4
[0078] This comparative example provides a solderless diffusion-welded reaction sintered silicon carbide special ceramic component and its preparation method. The difference between this example and Example 1 is that the hexagonal boron nitride and alumina composite coating spraying step is not performed in S1. Other process parameters and operating conditions are exactly the same as in Example 1.
[0079] The performance of the solderless diffusion-welded reaction-sintered silicon carbide special ceramic components prepared in Examples 1-4 and Comparative Examples 1-4 were tested. The specific test methods are as follows:
[0080] The test method for shear strength is ASTM C1469;
[0081] The high-temperature bending strength test method is GB / T 14390;
[0082] The test method for residual free Si content is ISO 21068.
[0083] The test results are shown in Table 1.
[0084] Table 1. Test results of reaction-sintered silicon carbide special ceramic components of Examples 1-4 and Comparative Examples 1-4
[0085]
[0086] As shown in Table 1, compared with Example 1, Comparative Example 1 showed a decrease in shear strength, a decrease in high-temperature bending strength, and an increase in residual free Si content; Comparative Example 2 showed a decrease in shear strength, a decrease in high-temperature bending strength, and an increase in residual free Si content; Comparative Example 3 showed a decrease in shear strength, a decrease in high-temperature bending strength, and an increase in residual free Si content; and Comparative Example 4 showed a decrease in shear strength, a decrease in high-temperature bending strength, and an increase in residual free Si content.
[0087] This is because Comparative Example 1, without femtosecond laser processing, lacks the directional silicon-locking effect provided by ordered capillary channels and rough groove walls at the interface. Liquid silicon diffuses and permeates within the matrix pores, increasing the thickness of the reaction zone and causing uneven microstructure. Localized free Si enrichment coexists with porosity, leading to decreased weld density and interface continuity, as well as reduced shear strength and high-temperature strength. Comparative Example 2 lacks the nano-carbon black and β-SiC whiskers introduced by suspension A, resulting in fewer highly active carbon sources and SiC nuclei at the interface, insufficient refinement, decreased free Si consumption efficiency, and reduced shear strength and high-temperature strength. Comparative Example 3, without the S3 step, has interface carbon sources primarily consisting of carbon black and matrix graphite. It lacks the continuous glassy carbon framework formed by the carbonization of phenolic resin in suspension B, as well as the multi-level carbon network composed of mesophase carbon microspheres and flake graphite. The interface region cannot generate a continuous silicon carbide solid-phase network sufficient to seal the permeation channels through the in-situ reaction of liquid silicon and carbon sources. Therefore, a large proportion of the liquid silicon remains as free Si after the reaction, resulting in an increase in residual free Si. Comparative Example 4 did not undergo the hexagonal boron nitride and alumina composite coating spraying step. During the molten stage, the pre-embedded metallic silicon could seep out along the side and bottom pores, reducing the effective silicon amount near the interface, decreasing the continuity and filling degree of SiC inside the weld, and reducing the shear strength and high-temperature bending strength.
[0088] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component, characterized in that, The preparation method includes: S1, α-SiC powder, colloidal graphite powder, PMMA microspheres and metallic silicon powder are dry mixed, and then PVA aqueous solution is added to granulate to obtain granulated powder. Cold isostatic pressing is used to obtain green blank. The end face of the green blank to be welded is placed in a femtosecond laser processing equipment for laser processing. After the laser processing is completed, hexagonal boron nitride powder and alumina powder are dispersed in an ethanol aqueous solution to obtain a slurry. The slurry is sprayed on the non-welding surface of the green blank and dried to obtain a blank. S2, mix anhydrous ethanol, n-butanol and deionized water, add carbon black N330, β-SiC whiskers and polyethyleneimine to obtain suspension A, vertically immerse the end face of the blank to be welded into suspension A, vacuum pressure, and dry to obtain green blank A. S3, thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder and silicon powder are added to anhydrous ethanol to obtain suspension B. Suspension B is screen printed on the end face of the green blank A to be welded and dried to obtain the treated green blank. S4. Place two processed green blanks on an optical alignment platform and perform an alignment step to obtain an assembly. Place the assembly into a vacuum carbon tube furnace and perform a sintering process to obtain a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component.
2. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S1: The mass ratio of α-SiC powder, colloidal graphite powder, PMMA microspheres, metallic silicon powder and PVA aqueous solution is (85-91):(5-6):(5-6):(15-17):(5-10).
3. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S1: The laser processing uses a wavelength of 1020-1040 nm, a pulse width of 250-300 fs, and a surface energy of 0.2-0.5 J / cm². 2 Laser scanning is performed with processing parameters of 100-300 mm / s to obtain concentric ring or orthogonal grid microgroove structures with groove width of 18-22 μm, groove depth of 28-32 μm, and groove spacing of 90-110 μm.
4. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S1: The mass ratio of the hexagonal boron nitride powder, alumina powder and ethanol aqueous solution is (3-5):(6-8):(30-40), and the mass fraction of the ethanol aqueous solution is 50 wt.%.
5. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S2: The mass ratio of anhydrous ethanol, n-butanol, deionized water, carbon black N330, β-SiC whiskers to polyethyleneimine is (30-36):(10-12):(5-10):(3-4):(1-2):(0.3-0.5).
6. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S3: The mass ratio of the thermosetting phenolic resin, mesophase carbon microspheres, flake graphite powder, silicon powder and anhydrous ethanol is (15-20):(5-7):(3-5):(1-2):(20-30).
7. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S3: The viscosity of the suspension B at 25±2℃ is 2000-3000 mPa·s.
8. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S4: The alignment step is as follows: adjust the position so that the coaxiality deviation of the two end faces to be welded is controlled to be no more than 10μm. After alignment, transfer the component to the graphite tooling fixture for clamping and fixing. Apply an axial load of 8-10MPa along the normal direction of the welding end face through a screw or hydraulic device, and maintain the loading state for 5-10 minutes to complete the pre-tightening and positioning.
9. The method for preparing a solderless diffusion-welded reaction-sintered silicon carbide special ceramic component according to claim 1, characterized in that, In S4: The sintering procedure is as follows: Ar is introduced at a flow rate of 300-600 sccm, the absolute pressure in the furnace is adjusted to 400-600 Pa, the temperature is increased from room temperature to 600-620℃ at a rate of 1℃ / min and held for 60-70 min, then increased to 900-920℃ at a rate of 2℃ / min, then the gas intake is stopped and the vacuum system is activated to evacuate the furnace to a dynamic vacuum state, then the temperature is increased to 1415-1425℃ at a rate of 5℃ / min, and within this temperature range, Ar is introduced, adjusting the furnace pressure to 0.09-0. At 0.11 MPa, under an Ar atmosphere, the temperature is increased to 1450-1460℃ at a rate of 2℃ / min, then increased to 1540-1560℃ at the same rate and held for 25-35 min. Subsequently, the temperature is increased to 1590-1610℃ and held for 25-35 min to complete the reaction sintering. After sintering, the furnace temperature is reduced to 1340-1360℃ at a cooling rate of 5℃ / min and held in this temperature range for 55-65 min. The heating power is then turned off while maintaining the Ar protective atmosphere, and the furnace is cooled to room temperature.
10. A solderless diffusion-welded reaction-sintered silicon carbide special ceramic component is obtained by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Method of co-sintering joined silicon-carbide-based composite ceramic green bodies
CN105130445A
Composite Component Modifications
CN110577414A
